Effect of Chamfer Angle on the Calibration Curves of Five Hole Probes - Nekkanti Sitaram; Kancherla Srikanth (International Journal of Rotating Machinery)
Five hole probes are extensively used for measurement of total and static pressures, flow angles, velocity and its components in turbomachinery, and other aerodynamic flows. Their operating range is usually limited to 30–40° depending on the type of the probe head. The chamfer angle of the probe is usually taken around 45°. Recent studies on three hole probes have shown that 30° chamfer angle is desirable for unsteady flow measurements. Hence the present investigation is undertaken to find the optimum chamfer angle of five-hole probes. A special five-hole probe of 9.6 mm head diameter and 3 mm diameter pressure take off tubes was designed and fabricated. The large size of the probe was chosen to minimize machining inaccuracies. The probe chamfer angle was varied from 30° to 60° in 5° steps. For each of the chamfer angles, the probe was calibrated in the range of −30° to +30° in 5° interval and the calibration curves are presented. In addition the sensitivities of the calibration coefficients are determined. It is concluded that five-hole probe with a chamfer angle 30° has large operating range, while five-hole probe with a chamfer angle of 50° has good sensitivity.